Prevalence And Associated Factors Of Visual Impairment Among School-Age Children In Bahir Dar City, Northwest Ethiopia - Merrie, Yosef Antehun; Tegegne, Mulusew Mulusew; Munaw, Minychil Bantihun; Alemu, Haile Woretaw (Clinical optometry (Auckland), 2019)
Visual impairment (VI) is one of the major public health problems in the world. It is highly prevalent among children in sub-Saharan countries, including Ethiopia. Worldwide, the magnitude of VI among school-age children is 1%-10%. However, there was limited information regarding the prevalence and associated factors of VI among school-age children in the study area, which is essential to plan and implement appropriate interventions. The aim of this study was to determine the prevalence and associated factors of VI among school-age children livin g in Bahir Dar city, northwest Ethiopia. A community-based cross-sectional study was done on a sample of 632 school-age children selected by multistage sampling in Bahir Dar from April 30 to May 15, 2018. Data were collected through interviews and physical examinations. Face-to-face interviews were done with a pretested semistructured questionnaire. Physical examinations were done with visual acuity measures and assessment of ocular pathology by optometrists. Data were entered into Epi Info 7 and exported to and analyzed with SPSS 20. Binary logistic regression was fitted, and variables with <0.05 in the multivariate model were considered statistically significant. A total of 601 study subjects were included in this study, giving a response rate of 95.2%. The median age was 13 (IQR 11-16) years, and 303 (50.3%) were male. Prevalence of VI was 52 (8.7%, 95% CI 6.2%-10.7%). In multivariate analysis, prematurity [AOR 2.8 (95% CI 1.19-6.83)], admission to a neonatal intensive-care unit (AOR 5.5, 95% CI 2.01-15.15), having a parent with VI (AOR 1.8, 95% CI 0.13-0.97), watching television from <2 m (AOR 8.7, 95% CI 1.49-18.24), and mobile-phone exposure >4 hours per day (AOR 1.6, 95% CI 1.32-4.45) were factors significantly associated with VI. The prevalence of VI among school-age children in Bahir Dar was significant. Premature birth, admission to a neonatal intensive-care unit, having a parent with VI, watching television from <2 m, and mobile exposure >4 hours per day were significantly associated.